Towards higher yield and quality of essential oils extracted from lemon myrtle (Backhousia citriodora) leaves via ohmic heated extraction - Hamzah, Muhammad Hazwan; Aminudin, Nur Haniem; Hamzah, Adila Fazliyana Aili; Ashari, Rozzamri; Md Ali, Abd Halim; Gavahian, Mohsen; Che Man, Hasfalina; Ying, Goh Sin; Wan Razali, Wan Aizuddin; Al-Sharify, Zainab T. (Springer, 2025)
This work aims to determine the optimal parameters for ohmic heated extraction (OHE) using Response Surface Methodology (RSM) to maximize oil yield from lemon myrtle. It also compares the effectiveness of OHE with hydro and steam distillation, evaluating them based on the oil yield, the physico-chemical properties of the lemon myrtle oil, and the morphological characteristics of the lemon myrtle itself. The optimal parameters for extracting lemon myrtle oil using OHE were determined to be 50 V, 63.1 °C, and a reaction time of 17 min. The RSM prediction for maximum oil yield was 0.52%, whereas the experimental results demonstrated a yield of 0.53 ± 0.08%. The study revealed that OHE achieved a lemon myrtle oil yield of 2.872 mL/kWh, outperforming hydro distillation at 0.511 mL/kWh and steam distillation at 0.033 mL/kWh. The oil extracted via OHE had a greenish-yellow colour, a refractive index of 1.334, and a specific gravity of 0.65. Conversely, the oils obtained from the other two methods exhibited a yellowish colour, with a refractive index of 1.333. The specific gravities were 0.64 for hydro distillation and 0.62 for steam distillation. Gas Chromatography-Mass Spectrometry analysis identified neral and α-citral as the major components in the OHE-extracted oil. Scanning Electron Microscopy indicated that OHE induced substantial structural changes in the samples, transforming their surfaces from rough to more aggregated due to the electric current used during extraction. This study suggests that OHE could be a highly effective alternative to traditional extraction methods with the capability of reducing energy consumption and enhancing production yield.